Attrition and health in ageing studies: Evidence from ELSA and HRS - James Banks; Alastair Muriel; James P. Smith (Institute for the Study of Labor (IZA), 2010)
In this paper we present results of an investigation into observable characteristics associated with attrition in ELSA and the HRS, with a particular focus on whether attrition is systematically related to health outcomes and socioeconomic status (SES). Investigating the links between health and SES is one of the primary goals of the ELSA and HRS, so attrition correlated with these outcomes is a critical concern. We explored some possible reasons for these differences. Survey maturity, mobility, respondent burden, interviewer quality, and differing sampling methods all fail to account for the gap. Differential respondent incentives may play some role, but the impact of respondent incentive is difficult to test. Apparently, cultural differences between the US and Europe population in agreeing to participate and remain in scientific surveys are a more likely explanation.
Keywords: I0; 330; health; attrition; Altersforschung; Befragung; Gesundheit; Sozialer Status; USA; Europa